Empowering Teachers with Kahoot-Based Media for Engaging Learning in Majene - Musfirah; Imron Burhan; Yulia; Abdul Hakim (Help: Journal of Community Service, 2024)
This community service program aimed to enhance the competence of teachers at SD Negeri 19 Rangas, Majene Regency, in utilizing Kahoot, an interactive and engaging online learning platform, to address the challenges of online education and improve teaching quality. The program employed a combination of lectures, hands-on practice, discussions, and evaluations. Conducted on July 13, 2023, the training involved 18 participants and emphasized practical engagement to ensure effective skill development. The training achieved a 90% attendance rate and demonstrated high enthusiasm among participants, as reflected in active participation during practical sessions and discussions. Evaluations indicated an 85% understanding of the processes and a 90% success rate in achieving learning objectives. The program effectively enhanced teachers’ capacity to integrate Kahoot into their teaching, fostering interactive and engaging learning environments. It addressed key online learning challenges, such as lack of engagement, while improving pedagogical outcomes. The training successfully equipped teachers with the necessary skills to utilize Kahoot as an innovative learning tool, contributing to improved teaching practices and student engagement in online education.